Supply Chain Performance Analysis of Corn Processed Animal Feed - Faiz Ahmad Sibuea; Mhd.Buhari Sibuea; Abdul Rahman; Agustian Hartanto (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
The purpose of this study was to analyze the general description of the corn supply chain as a raw material for animal feed in the research area using the Food Supply Chain Networks (FSCN) model, to analyze the performance of the supply chain for corn as a raw material for animal feed in the study area using the Analytical Hierarchy Process (AHP) method. The samples in the research were farmers (raw material suppliers), animal feed entrepreneurs, animal feed traders and breeders consisting of 7 farmers (raw material suppliers), 5 animal feed entrepreneurs, 10 animal feed traders and 8 breeders with the research location is in the Simalungun Regency. Based on the results of the study it can be concluded that in general, the supply chain for corn as a raw material for animal feed in this study area is farmers (raw material suppliers) - animal feed entrepreneurs - animal feed traders - breeders (consumers). From a business point of view, the supply chain for corn as a raw material for animal feed has carried out two business processes, namely procurement and customer orders. Supply chain performance in the study area is quite consistent with a consistency ratio value of 0.015. The value points that there is good cooperation from partnerships such as raw material suppliers who are currently still able to meet demands from entrepreneurs, then the consistency obtained from this method is also related to a workforce that is skilled enough to help develop businesses and can support the development of product marketing.